Fabrication and characterization of graphene-on-silicon schottky diode for advanced power electronic design - Mohd Rofei Mat Hussin,; Muhammad Mahyiddin Ramli,; Sharaifah Kamariah Wan Sabli,; Iskhandar Md Nasir,; Mohd Ismahadi Syono,; Wong, H.Y.; Mukter Zaman, (Penerbit Universiti Kebangsaan Malaysia, 2017)
In this study, graphene-on-silicon process technology was developed to fabricate a power rectifier Schottky diode for efficiency improvement in high operating temperature. Trench-MOS-Barrier-Schottky (TMBS) diode structure was used to enhance the device performance. The main objective of this research was to study the effect of reduced graphene oxide (RGO) deposited on silicon surface for Schottky barrier formation and heat transfer in Schottky junction. The study showed RGO deposited on silicon as a heat spreader could help to reduce the effect of heat generated in the Schottky junction that leads to a leakage current reduction and efficiency improvement in the device. With comparison to the conventional metal silicide (titanium silicide and cobalt silicide), the leakage reduced by two-orders of magnitude when tested under high operating temperature (>100°C). TMBS rectifier diode that uses graphene-based heat spreader could produce highly reliable product able to withstand high temperature operating condition.